Pengenalan Kebiasaan Cuci Tangan Dengan Sabun Sebagai Inisiatif Kesehatan di Sekolah Dasar - Pratami, Arsya Rine; Nugraheni, Nursiwi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Elementary school age children are often faced with problems related to dental and oral health, Clean and Healthy Living Behavior (PHBS), and Hand Washing Behavior with Soap (CTPS). The health of elementary school-aged children can be positively impacted through the implementation of health education strategies, such as education about hand washing with soap (CTPS) which influences hand washing attitudes in elementary school students. This research is a literature review research, where the author searches various relevant sources, such as journals, books, articles, the internet, or documents related to the topic under study. From the analysis of various published scientific research journals such as those conducted by Merlina (2018), there are still students (29.3%) who have a poor level of knowledge about (CTPS), 37% do not know the need to wash their hands with soap, 50% do not know why do you have to wash your hands with soap, 35.9% don't know where to wash their hands, and 15.2% don't know the importance of CTPS. The habit of washing your hands with soap regularly can help reduce the risk of contracting diseases that are often transmitted to children in the school environment, such as diarrhea. Good hand washing habits not only protect children from infectious diseases, but also help children acquire healthy living habits that can last throughout the child's life.